TRANSDERMAL DRUG DELIVERY SYSTEM: TRANSDERMAL PATCH AN EFFECTIVE APPROACH TO TREAT MIGRAINE. - Kehar Singh; Dr. Gaikwad Dushyant Dadabhau; Satbir Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
In January 2013, the US Food and Drug Administration approved an iontophoretic transdermal system (ITS) (skin patch) formulation of sumatriptan for the immediate treatment of migraine attacks. Migraine is one of the most common primary headache disorders, affecting around 12% of the general population in Western countries. Merriam Webster indicates that the term "transdermal" is very new to the field of medicine and pharmacology, dating it to 1944. Transdermal medications come in a discreet, self-contained dose form. Drug distribution via skin to have a systemic impact without causing variations in the drug’s plasma concentration. The topical distribution of therapeutic agents presents numerous benefits in comparison to traditional oral and invasive drug delivery techniques.further offer a prolonged amount of time for the drug’s controlled release. This review article discusses the benefits of transdermal drug delivery systems (TDDS) as ionopheretic transdermal system for treatment of acute migraine attacks, use of Sumatriptan as the most effective drug product to treatment of migraine, skin pathways for TDDS, different transdermal patch components, preparation methods, transdermal system evaluation, general clinical considerations when using TDDS, and limitations of TDDS.